2010
DOI: 10.1116/1.3511509
|View full text |Cite
|
Sign up to set email alerts
|

Gas field ion source and liquid metal ion source charged particle material interaction study for semiconductor nanomachining applications

Abstract: Semiconductor manufacturing technology nodes will evolve to the 22, 15, and 11 nm generations in the next few years. For semiconductor nanomachining applications, further beam spot size scaling is required beyond what is capable by present generation Ga+ focused ion beam technology. As a result, continued Ga+ beam scaling and/or alternative beam technology innovations will be required. In this work, several alternative ion beam technologies are explored and compared to Ga+ beam for key nanomachining and substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 13 publications
1
43
0
Order By: Relevance
“…As silicon changes from crystalline to amorphous above a well-defined disorder threshold, the observed shape in the TEM is a good indicator of the range of ions. By comparing the shape of the bell-like amorphous region with the MC simulation, it was thus possible to confirm that the N 2 molecules are ionized to N þ 2 .As energetic ions are instantaneously neutralized upon impact onto a solid through the pickup of an electron, the impact of a N 2 molecule onto silicon was calculated by atomistic simulation as well [39]. It confirmed that the N-N bond is broken within a few atomic layer, and the N atoms Figure 5.…”
Section: Field Ionization Of Molecular Nitrogen Gas and Solid-ion Intmentioning
confidence: 99%
See 1 more Smart Citation
“…As silicon changes from crystalline to amorphous above a well-defined disorder threshold, the observed shape in the TEM is a good indicator of the range of ions. By comparing the shape of the bell-like amorphous region with the MC simulation, it was thus possible to confirm that the N 2 molecules are ionized to N þ 2 .As energetic ions are instantaneously neutralized upon impact onto a solid through the pickup of an electron, the impact of a N 2 molecule onto silicon was calculated by atomistic simulation as well [39]. It confirmed that the N-N bond is broken within a few atomic layer, and the N atoms Figure 5.…”
Section: Field Ionization Of Molecular Nitrogen Gas and Solid-ion Intmentioning
confidence: 99%
“…(g) Atomic resolution HAADF-STEM image of the area indicated by the rectangle in (a), which shows the dumbbell structure of Si(110). Reprinted with permission [39]. Copyright 2017, American Vacuum Society.…”
Section: Field Ionization Of Molecular Nitrogen Gas and Solid-ion Intmentioning
confidence: 99%
“…Recent advances in novel ion beam technologies seem poised to negate these drawbacks of traditional LMIS FIB systems. The most advanced technology so far has been gas field‐ionization sources (GFIS), in which an atomically sharp tungsten tip is used to ionize light noble gas species, which are then used for imaging and milling (Tan et al ., ). This technology is potentially advantageous for TEM sample preparation as compared to a Ga FIB for two reasons.…”
Section: Introductionmentioning
confidence: 97%
“…Secondly, as He and Ne are noble gases with low atomic weights, they do not form alloys in metallic materials or concentrate into precipitates that could obscure imaging in the TEM. The drawbacks and the damage caused by the GFIS beams are less well understood, but bubble formation has been found to occur after milling with both He and Ne (Tan et al ., ; Gonzalez et al ., ). The focus of this work is to compare the damage from a Ne GFIS beam with a traditional Ga LMIS FIB to evaluate its efficacy in TEM sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The attempt of performing BS in a HIM is connected to a very small beam size and low primary ion energies. It thus is clear that in order to prevent sample damage (by sputtering and/or bubble formation [26][27][28][29]) backscattered particle detection has to be sensitive to both backscattered ions as well as neutrals.…”
Section: Introductionmentioning
confidence: 99%